2009
DOI: 10.1111/j.1471-4159.2009.06310.x
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of intracellular copper trafficking pathway in a mouse model of mutant copper/zinc superoxide dismutase‐linked familial amyotrophic lateral sclerosis

Abstract: Mutations in copper/zinc superoxide dismutase (SOD1) are responsible for 20% of familial amyotrophic lateral sclerosis through a gain‐of‐toxic function. We have recently shown that ammonium tetrathiomolybdate, an intracellular copper‐chelating reagent, has an excellent therapeutic benefit in a mouse model for amyotrophic lateral sclerosis. This finding suggests that mutant SOD1 might disrupt intracellular copper homeostasis. In this study, we investigated the effects of mutant SOD1 on the components of the cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 56 publications
1
55
0
Order By: Relevance
“…This finding supports the idea that SOD1 plays a role in normal metal homeostasis. Interestingly, a recent study by Tokuda et al (72) revealed that major alterations in copper homeostasis were associated with G93A hSOD1.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports the idea that SOD1 plays a role in normal metal homeostasis. Interestingly, a recent study by Tokuda et al (72) revealed that major alterations in copper homeostasis were associated with G93A hSOD1.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the copper uptake proteins, STEAP2 and CTR1, is increased, whereas that of the copper efflux protein, ATP7A, is decreased in the spinal cord of mutant SOD1 mice, regardless of their copper-binding ability [6]. This impairment of the copper trafficking system results in the accumulation of copper ions in the spinal cord [6][7][8][9][10]. The therapeutic effects of copperEiichi Tokuda and Shunsuke Watanabe contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…The deletion of MT-I/-II significantly exacerbated the disease course, including disease onset (88±2. 9 …”
Section: Dex Induces Mt-i/-ii In Spinal Cord Astrocytes and Microgliamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently shown, in the spinal cord of transgenic mice, that a mutant SOD1 associated with fALS (namely G93A) affects the expression of copper chaperones, also sequestering some of them in aggregates, thus disrupting intracellular copper homeostasis (Tokuda et al 2009).…”
mentioning
confidence: 99%